Genotype characteristics of Y-chromosome in the Balkan population: review of haplogroup frequencies - Jankova, Renata; Jovchevska, Ivana; Kouter, Katarina; Filipova, Silvana; Videtič Paska, Alja (Informa UK Limited, 2024)
The genetic structure of the Balkan peoples is complex and is reflection of continuous migration processes and settlement of various tribes and ethnic groups throughout past centuries. The human uniparental genetic markers, the Y-chromosome and mitochondrial DNA are widely used for studying population heterogeneity, human migration processes and recently, as important markers in forensic cases. Y-chromosome short tandem repeats (Y-STRs) and single nucleotide polymorphisms (Y-SNPs) are used to find the origin of bio-geographic ancestry of individuals and populations. Except in understanding of population origins from an evolutionary perspective, determination of the Y-chromosome haplogroups distribution is of great importance in forensic cases, since it is suitable to provide information about paternal biogeographical ancestry of unknown perpetrators or missing persons in cases where autosomal DNA profiling is uninformative. Published results show that the population of the Balkans is mostly characterized by Y-chromosome haplogroups I, R and E. The most frequent are haplogroups I2, R1a and E1b1b descending from Europe, west Asia and Africa, respectively. The aims of this article are to present Y-chromosome haplogroups that are predominant in population of the Balkans, and give an overview of their distribution for application in population studies, forensic cases and as documents of evolutionary history.
Keywords: Population of the Balkans; Y-SNP haplogroups; forensic application